Ճշմարտության որոնումն անհատի դրամայում - Անուշ Լալայան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Образы Айвазяна справедливость находят в личном понятии действительности. Каков внутренний мир человека, каково его восприятие действительности, таково и его отношение к миру. Справедливость Айвазяна основана на библейских заветах, которая в одном случае, заключается в там, чтобы думать, а в другом-воспитывать. В драме личности поиск справедливости разрешается в победе над собой. Ayvazian’s characters reveal the truth by individually perceiving the reality. What the inner world, emotions, perceptions and the depth of penetration of a human are, so is his behavior towards the world. The truth, according to Ayvazian, is based on biblical commandments which is called in one case to think, to ponder and in another case to bring up. On the basis of the individual’s drama is the problem of the searching for the truth which resolves by self-overcoming.
Keywords: Literature